Distributed agency in second language learning and teaching through generative AI - Godwin-Jones, Robert (Language learning & technology, 2024)
Generative AI offers significant opportunities for language learning. Tools like ChatGPT provide second language practice through chats in written or voice formats, with the learner specifying through prompts conversational parameters. AI can be instructed to give corrective feedback and create practice exercises. Using AI, instructors can build learning and assessment materials in a variety of media. Generative AI provides affordances for both autonomous and instructed learning. In addition, AI is poised to enhance dramatically the usefulness of immersive technologies. For both learners and teachers, it is important to understand the limitations of AI systems that arise from their statistical model of human language, which constrains their capacity for dealing with sociocultural aspects of language use. Additionally, there are ethical concerns over how AI systems are created and deployed, as well as practical constraints in their use, especially for less privileged populations. Nevertheless, the power and versatility of AI tools are likely to turn them into constant companions in many people’s lives, creating a close connection that goes beyond simple tool use. Ecological theories such as sociomaterialism are helpful in examining the shared agency that develops through close user-AI interactions, as are the perspectives on human-tool relationships from Indigenous cultures.